Effectiveness of Discharge Planning Interventions on Hospital Readmission Among Patients with Pulmonary Tuberculosis: A Scoping Review - Risma Amalia Safitri; Suriadi Jais; Haryanto Haryanto; Wida Kuswida Bhakti (Borneo Nursing Journal (BNJ), 2026)
Pulmonary tuberculosis remains a major cause of morbidity and health-system burden, particularly in low- and middle-income countries. Despite advances in antituberculosis therapy, the transition from hospital to community is often fragmented, increasing the risk of complications, treatment interruption, and hospital readmission. Discharge planning is increasingly recognized as a peri-discharge intervention that may reduce readmission by supporting treatment continuity, complication monitoring, patient understanding, family involvement, and post-discharge follow-up. This literature review was conducted as part of a scoping review framework following the PRISMA extension for Scoping Reviews (PRISMA-ScR) and Joanna Briggs Institute methodological guidance. Literature searches were performed in PubMed, Scopus, Web of Science, and CINAHL. Out of 500 identified articles, 11 studies were included after screening and eligibility assessment. Discharge planning for pulmonary tuberculosis is implemented through nurse-led education, counseling, medication guidance, readiness assessment, family engagement, and continuity of care arrangements. Available evidence indicates that structured nursing interventions are associated with improved knowledge, self-care, adherence, discharge readiness, and lower short-term readmission risk. Five thematic domains were identified: nurse-led interventions, core components, discharge readiness, continuity of care, and socioeconomic/psychosocial barriers. Discharge planning may contribute to lowering readmission among pulmonary tuberculosis patients, but current evidence remains indirect and heterogeneous. Rigorous TB-specific studies with readmission as the primary outcome are urgently needed.